Weaving flexible gender scripts and cultural transmission: maternal agency in Kampung Chetti. - Wong, Yee Von; Lai, Suat Yan; Somiah, Vilashini (Gender, Place & Culture: A Journal of Feminist Geography, 2026)
This study explores the cultural transmission practices of eleven (11) Chetti Melaka mothers who, despite themselves not being originally from the community, actively sustains and adapts cultural traditions within their intercultural marriages. Drawing on gendered socialisation, intersectionality, and spatial theory, this research conceptualises mothers as active 'directors of cultural transmission'; they strategically shape practices in response to gender, space, and familial dynamics. Kampung Chetti emerges as a relational and processual space where cultural expectations are blended, redefined, and at times resisted. Through nuanced practices, such as invoking symbolic paternal authority, reshaping naming conventions, and tailoring educational strategies, these mothers challenge rigid gender scripts. Sons are often positioned as custodians of ritual culture, while daughters take on hybrid roles that reflect evolving maternal agency. This study, however, offers a novel perspective on flexible gender scripts, where sons may also be socialised into preserving maternal cultural traditions, and daughters, in the absence of sons, may assume ritual responsibilities. These findings contribute to broader discussions on cultural transmission, maternal agency, gendered socialisation, and the role of place in hybrid family practices within Malaysia's multicultural context.